Food needs and health behaviors in the COVID-19 situation: a case study of quarantined communities in densely populated areas of Bangkok, Thailand - Areeya Jirathananuwat; Suteera Saenmontrikul; Arunee Hengyotmark; Krittanan Pensirisomboon (Journal of Health, Population and Nutrition)
Abstract Background The Thai government’s initial response to the novel coronavirus disease 2019 (COVID-19) led to confusion and food insecurity in quarantined low-income communities. Although free food programs were initiated, no official assessment of their impact exists. The objective of this study was to evaluate the effectiveness of these food programs by surveying the food requirements, food needs, and health behaviors of quarantined, densely populated communities in Bangkok. Methods A cross-sectional descriptive study was conducted with 410 urban dwellers from quarantined communities who received free food assistance. Data were collected via a questionnaire on food requirements, food hygiene, food needs, and health behaviors during the COVID-19 epidemic. The data were analyzed in terms of frequency, percentage, mean, and standard deviation. The associations between demographic characteristics, food needs, and health behaviors were analyzed using logistic regression. Results The participants demanded dried/canned food (54.9%) and three meals per day (64.9%), while the majority of the food provided consisted of rice and side dishes (96.2%) that were clean and qualified. In consideration of food needs, a high level of demand was observed in the first three levels: enough food, acceptable food, and reliability. Overall, dietary health behaviors were good. Logistic regression analysis revealed that being elderly (AOR = 3.67, 95% CI = 1.63–8.27) and having a moderate to high income level (AOR = 3.93, 95% CI = 2.23–6.94) were positively correlated with food needs. Similarly, good health behaviors were positively correlated with being female (AOR = 1.74, 95% CI = 1.12–2.69), being elderly (AOR = 3.73, 95% CI = 1.72–8.08), and having a moderate to high income level (AOR = 3.76, 95% CI = 2.38–5.93). Conclusions Preparing for future crises requires the consideration of demographic factors that influence food needs, personal choices, and dietary health behaviors. Future food assistance programs should focus on the provision of nonperishable and long-lasting food, which will ensure the consistent availability of three meals per day.